Secondary battery and electronic apparatus including secondary battery

By using levulinic acid and propulinic acid as organic solvents in the electrolyte of lithium-ion batteries and controlling the difference in their mass fractions, the problem of unstable batteries at high temperatures and high pressures is solved, and the battery's high temperature and high pressure stability and cycling performance are improved.

JP2025038117AActive Publication Date: 2025-03-18NINGDE AMPEREX TECHNOLOGY LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024220728
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-12-19
Filing Date
2024-12-17
Publication Date
2025-03-18
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

Existing secondary batteries (such as lithium-ion batteries) show unstability at high temperatures and high pressures, resulting in unstable structural structure of the negative electrode material pattern, which in turn affects the performance of the battery.

Method used

By using levulinic acid and propulinic acid as organic solvents in the electrolyte of the battery and controlling the difference in their mass fractions, it forms a low-impedance protective layer on the negative electrode material pattern, thereby improving the high temperature and high pressure stability of the battery.

Benefits of technology

It effectively reduces the internal resistance of the battery and improves the cycling performance and low-temperature rate performance of the battery under high temperature and high voltage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038117000001
    Figure 2025038117000001
  • Figure 2025038117000002
    Figure 2025038117000002
  • Figure 2025038117000003
    Figure 2025038117000003
Patent Text Reader

Abstract

To provide a secondary battery that reduces a high-temperature internal resistance to improve cycle performance at high voltage, and an electronic apparatus including the secondary battery.SOLUTION: A secondary battery includes a positive electrode, a negative electrode, and an electrolyte. The electrolyte includes an organic solvent, and the organic solvent includes ethyl propionate and propyl propionate. When the mass content of ethyl propionate in the electrolyte is defined as m%, and the mass content of propyl propionate as n%, the difference between n and m (n-m) is 5-54. The negative electrode includes a negative electrode collector, and a negative electrode active material layer provided in the negative electrode collector. The negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes graphite, and n and the Lc value of graphite satisfy that the ratio n / Lc is 1-2.14. The difference in the content between ethyl propionate and propyl propionate included in the electrolyte satisfies a specific request, and the ratio of the mass content n% of propyl propionate to the Lc of graphite (n / Lc) is 1-2.14.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of battery technology, and more particularly to a secondary battery and an electronic device including the secondary battery. [Background technology]

[0002] Secondary batteries such as lithium-ion batteries have the advantages of being environmentally friendly, having high energy density, and having a long cycle life, and are therefore widely used in mobile phones, personal computers, wearable devices, consumer drones, power tools, electric motorcycles, electric vehicles, or large energy storage devices. As the market continues to expand, the requirements for battery properties also continue to increase, for example, the requirements for battery properties under high and low temperature conditions are increasing day by day. Currently, the electrolyte of secondary batteries often selects carbonate ester compounds as a solvent system, but the high voltage stability of such secondary batteries is relatively poor, and the structure of the graphite material of the negative electrode is easily unstable, resulting in a decrease in performance. Therefore, the performance of secondary batteries needs to be further improved. Summary of the Invention

[0003] In view of this, a first aspect of the present invention provides a secondary battery, the secondary battery comprising a positive electrode, a negative electrode, and an electrolytic solution, the electrolytic solution comprising an organic solvent, the organic solvent comprising ethyl propionate and propyl propionate, a difference nm between n and m being 5 to 54, where a mass content of the ethyl propionate is m% and a mass content of the propyl propionate is n% relative to a mass of the electrolytic solution, The negative electrode includes a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes graphite at a mass content of 90% or more, and a ratio of n to an Lc value of the graphite satisfies n / Lc of 1 to 2.14.

[0004] In the secondary battery of the present invention, the difference between the contents of ethyl propionate and propyl propionate in the electrolyte is set to satisfy the above-mentioned specific requirements, so that the propyl propionate with a relatively high content exhibits low impedance characteristics at low temperatures and can increase the transmission speed of active ions, and the ethyl propionate and propyl propionate at high temperatures and high voltages reduce corrosion due to oxidation of the graphite surface, reduce the consumption of active lithium, reduce the internal resistance of the secondary battery, reduce the high-temperature internal resistance, and improve the cycle performance at high voltage. In addition, the Lc of the graphite and the mass content n% of propyl propionate satisfy n / Lc of 1 to 2.14, so that the lithium ions have a relatively short absorption / desorption path and the low-temperature rate performance of the secondary battery can be improved.

[0005] In some embodiments, nm is 18 to 54. This can further improve the cycle performance at high voltage of the secondary battery and reduce the high temperature internal resistance. In some embodiments, nm is 21 to 47.

[0006] In some embodiments, the sum of n and m, m+n, is 42 to 70. By controlling the total mass content of both ethyl propionate and propyl propionate in the electrolyte to be within the above range, the internal impedance of the secondary battery can be further reduced, corrosion due to oxidation of the graphite surface can be reduced, and the high voltage cycle performance and low temperature rate performance of the secondary battery can be further improved. In some embodiments, m+n is 53 to 69. In some embodiments, m+n is 52 to 67.5.

[0007] In some embodiments, m is 8 to 24. This provides a better balance between the viscosity of the electrolyte and the effect of reducing the internal impedance of the secondary battery, and further improves the high voltage cycle performance and low temperature rate performance of the secondary battery. In some embodiments, m is 8 to 19. In some embodiments, m is 11 to 21.

[0008] In some embodiments, n is 29 to 62. This makes it possible to better balance the viscosity of the electrolyte and the effect of reducing the internal impedance of the secondary battery, and to further improve the high voltage cycle performance and low temperature rate performance of the secondary battery. In some embodiments, n is 33 to 58. In some embodiments, n is 30 to 53.5.

[0009] In some embodiments, the electrolyte further contains lithium bis(fluorosulfonyl)imide, and when the mass content of lithium bis(fluorosulfonyl)imide is p% relative to the mass of the electrolyte, p is 0.07 to 4.3. Lithium bis(fluorosulfonyl)imide has relatively high stability at high temperature and high voltage, inhibits decomposition of propyl propionate, and can form a protective film on the graphite surface that has low impedance, is stable, and is not easily oxidized, thereby further reducing the internal impedance of the secondary battery and further improving the high temperature characteristics of the secondary battery. In some embodiments, p is 0.7 to 2.4. In some embodiments, p is 1.3 to 3.5.

[0010] In some embodiments, the ratio of p to m, p / m, is 0.01 to 0.36. By controlling p / m to be within the above range, the transmission rate of active ions can be increased, the oxidation resistance of the graphite surface can be increased, and the performance of the secondary battery at high temperature and high voltage can be further improved. In some embodiments, p / m is 0.07 to 0.17. In some embodiments, p / m is 0.09 to 0.32.

[0011] In some embodiments, the Lc value of the graphite satisfies 25≦Lc≦38. By setting the Lc value of the graphite, the lithium ions have a relatively short absorption and desorption path in the graphite, improving the low-temperature rate performance of the secondary battery. The Lc of the graphite material is achieved by controlling the particle size of the raw material, the temperature of the graphitization treatment, etc., during the graphite preparation process. In some embodiments, the graphite includes at least one of artificial graphite and natural graphite.

[0012] In some embodiments, the electrolyte further contains lithium difluorophosphate, and the mass content of lithium difluorophosphate is 0.02% to 2.4% relative to the mass of the electrolyte. Adding lithium difluorophosphate to the electrolyte can enhance the film formation stability of ethyl propionate on the graphite surface at low temperatures, improving the performance at high temperatures and high voltages, and further improving the low-temperature rate performance of the secondary battery. In some embodiments, the mass content of lithium difluorophosphate is 0.2% to 1.6%.

[0013] In some embodiments, the electrolyte further contains 1,3-propane sultone, and the mass content of 1,3-propane sultone is 1.7% to 4.4% relative to the mass of the electrolyte. Adding 1,3-propane sultone to the electrolyte can prevent the formation of an excessively thick film of ethyl propionate on the graphite surface, further reducing the internal impedance of the secondary battery and improving the high and low temperature characteristics of the secondary battery. In some embodiments, the mass content of 1,3-propane sultone is 1.7% to 2.9%. In some embodiments, the mass content of 1,3-propane sultone is 3.1% to 3.9%.

[0014] A second aspect of the present invention provides an electronic device, the electronic device including the above-mentioned secondary battery. By using the above-mentioned secondary battery as a power supply source for the electronic device, the performance of the secondary battery is stabilized, and the electronic device can be stably supplied with power.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a secondary battery, which includes a positive electrode, a negative electrode, and an electrolyte, the electrolyte includes an organic solvent, the organic solvent includes ethyl propionate and propyl propionate, and when the mass content of ethyl propionate is m% and the mass content of propyl propionate is n% relative to the mass of the electrolyte, nm is 5 to 54, and in the negative electrode, the negative electrode active material includes graphite at a mass percentage content of 90% or more, and the ratio of n to the Lc value of graphite is n / Lc of 1 to 2.14. By controlling the difference in the content of ethyl propionate and propyl propionate contained in the electrolyte to satisfy the above specific requirements, it is possible to reduce corrosion due to oxidation of the graphite surface, reduce the consumption of active lithium, reduce the internal resistance of the secondary battery, reduce the high-temperature internal resistance, and improve the cycle performance at high voltage. In addition, it is possible to provide a relatively short absorption and release path for lithium ions and improve the low-temperature rate performance of the secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The following is a description of examples of the present invention. The range values ​​of the data described in the present invention should include the endpoints unless otherwise specified.

[0017] According to a first aspect of the present invention, the present invention provides a secondary battery, which includes a negative electrode, a positive electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode. The secondary battery may be a lithium ion battery or any other suitable secondary battery.

[0018] The electrolytic solution includes an organic solvent and an electrolyte. The negative electrode includes a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector. The positive electrode includes a positive electrode current collector and a positive electrode active material layer provided on at least one surface of the positive electrode current collector.

[0019] In the present invention, in order to obtain a secondary battery with stable performance, special improvements and limitations are made mainly to the contents of components in the electrolyte and the negative electrode active material (graphite) of the negative electrode.

[0020] In the present invention, the organic solvent of the electrolyte contains ethyl propionate and propyl propionate. In the electrolyte, the mass content of propyl propionate is greater than the mass content of ethyl propionate. In the present invention, when the mass content of ethyl propionate is m% and the mass content of propyl propionate is n% relative to the mass of the electrolyte, the difference nm between n and m is 5 to 54, that is, 5≦nm≦54 is satisfied. Preferably, the difference nm between n and m is 18 to 54, and preferably, nm is 21 to 47. For example, the difference nm between n and m may be 5, 11, 13, 17, 19, 23, 31, 34, 39, 47, 49, or 54, or may be a value within a range consisting of any two of these values.

[0021] The negative electrode active material layer mainly comprises a negative electrode active material. In the present invention, the negative electrode active material mainly comprises graphite, and the mass content of the graphite relative to the mass of the negative electrode active material is 90% or more. In some embodiments, the negative electrode active material is made of graphite. In other embodiments, the negative electrode active material is a mixture of graphite and silicon.

[0022] The Lc value of graphite is the crystallite size along the vertical axis of the graphite crystalline material measured by X-ray diffraction, and is expressed in nm. In the present invention, the ratio of the n value in the mass content of propyl propionate in the above-mentioned electrolyte to the Lc value of graphite satisfies n / Lc of 1 to 2.14, that is, 1≦n / Lc≦2.14. Preferably, n / Lc is 1.10 to 2.00. For example, n / Lc may be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.7, 1.9, 2.0, 2.1, or 2.14, or may be a value within a range consisting of any two of these values.

[0023] In secondary batteries, by setting the difference in the content of ethyl propionate and propyl propionate in the electrolyte to satisfy the above-mentioned specific requirements, the propyl propionate with a relatively high content exhibits low impedance characteristics at low temperatures and can increase the transmission speed of active ions, and the ethyl propionate and propyl propionate at high temperatures and high voltages reduce corrosion due to oxidation of the graphite surface, reduce the consumption of active lithium, reduce the internal resistance of the secondary battery, reduce the high-temperature internal resistance, and improve the cycle performance at high voltage. In addition, when the mass content n% of Lc of graphite and propyl propionate satisfy n / Lc of 1 to 2.14, it is possible to provide a relatively short absorption and desorption path for lithium ions and improve the low-temperature rate performance of the secondary battery.

[0024] In some embodiments, the Lc value of the graphite is 25 to 38, i.e., 25≦Lc≦38 is satisfied. For example, Lc may be 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, or 38, or a value within a range consisting of any two of these values. By setting the Lc value of the graphite, the lithium ions have a relatively short absorption and desorption path in the graphite, improving the low-temperature rate performance of the secondary battery. The Lc of the graphite material is achieved by controlling the particle size of the raw material, the temperature of the graphitization treatment, etc., during the graphite preparation process.

[0025] In some embodiments, the sum of n and m, n+m, is 42 to 70, i.e., 42≦m+n≦70 is satisfied, that is, the total mass content of both ethyl propionate and propyl propionate is 42% or more and 70% or less with respect to the mass of the electrolyte. Preferably, m+n is 42 to 70, more preferably, m+n is 53 to 69, and even more preferably, m+n is 52 to 67.5. For example, the sum of n and m, m+n, may be 42, 47, 51, 53, 57, 63, 64, 67, 69, or 70, or a value within a range consisting of any two of these values. When the total mass content of both ethyl propionate and propyl propionate in the electrolyte is within the above range, the internal impedance of the secondary battery can be further reduced, corrosion due to oxidation of the graphite surface can be reduced, and the high voltage cycle performance and low temperature rate performance of the secondary battery can be further improved.

[0026] In some embodiments, m is 8 to 24, i.e., 8≦m≦24 is satisfied, and the mass content of ethyl propionate is 8% or more and 24% or less with respect to the mass of the electrolyte. Preferably, m is 8 to 24, more preferably, m is 8 to 19, and even more preferably, m is 11 to 21. For example, m may be 8, 11, 13, 14, 16, 17, 19, 20, 21, 23, or 24, or a value within a range consisting of any two of these values. When the mass content of ethyl propionate satisfies the above range, the balance between the viscosity of the electrolyte and the effect of reducing the internal impedance of the secondary battery can be improved, and the high voltage cycle performance and low temperature rate performance of the secondary battery can be further improved.

[0027] In some embodiments, n is 29 to 62, i.e., 29≦n≦62 is satisfied, and the mass content of propyl propionate is 29% or more and 62% or less with respect to the mass of the electrolyte. Preferably, n is 29 to 62, more preferably, n is 33 to 58, and even more preferably, n is 30 to 53.5. For example, n may be 29, 31, 33, 37, 43, 47, 51, 53, 58, 61, or 62, or a value within a range consisting of any two of these values. When the mass content of propyl propionate satisfies the above range, the balance between the viscosity of the electrolyte and the effect of reducing the internal impedance of the secondary battery can be improved, and the high voltage cycle performance and low temperature rate performance of the secondary battery can be further improved.

[0028] In some embodiments, the electrolyte further includes lithium bis(fluorosulfonyl)imide (Li(N(SO2F)2, LiFSI). When the mass content of LiFSI is p% with respect to the mass of the electrolyte, p is 0.07 to 4.3, i.e., 0.07≦p≦4.3 is satisfied. Preferably, p is 0.7 to 2.4, and more preferably, p is 1.3 to 3.5. LiFSI has relatively high stability at high temperatures and high voltages, inhibits decomposition of propyl propionate at high voltages, and prevents graphite from being decomposed. A protective film having low impedance, stability, and resistance to oxidation can be formed on the surface. When LiFSI having the above mass content range is added to the electrolyte, the internal impedance of the secondary battery is further reduced, and the high-temperature characteristics of the secondary battery are further improved. For example, p may be 0.07, 0.1, 0.3, 0.7, 1.3, 1.7, 2.3, 2.7, 3.1, 3.3, 3.7, 4.1, or 4.3, or may be a value within a range consisting of any two of these values.

[0029] In some embodiments, the ratio p / m of p to m is 0.01 to 0.36, i.e., 0.01≦p / m≦0.36 is satisfied. Preferably, p / m is 0.07 to 0.17, more preferably, p / m is 0.09 to 0.32. For example, p / m may be 0.01, 0.07, 0.09, 0.13, 0.19, 0.23, 0.27, 0.31, 0.33, 0.35, or 0.36, or may be a value within a range consisting of any two of these values. When the ratio p / m of the mass content p% of LiFSI to the mass content m% of ethyl propionate satisfies the above range, the transmission rate of active ions can be increased, the oxidation resistance of the graphite surface can be increased, and the performance of the secondary battery at high temperature and high voltage can be further improved.

[0030] In some embodiments, the electrolyte further comprises lithium difluorophosphate. The mass content of lithium difluorophosphate is 0.02% to 2.4% relative to the mass of the electrolyte. Preferably, the mass content of lithium difluorophosphate is 0.2% to 1.6%. For example, the mass content of lithium difluorophosphate may be 0.02%, 0.2%, 0.7%, 0.9%, 1.1%, 1.7%, 1.9%, 2.1%, or 2.4%, or may be a value within a range consisting of any two of these values. Adding lithium difluorophosphate can enhance the film formation stability of LiFSI and ethyl propionate on the graphite surface at low temperatures, improve performance at high temperatures and high voltages, and further improve the low-temperature rate performance of the secondary battery.

[0031] In some embodiments, the electrolyte further comprises 1,3-propane sultone. The mass content of 1,3-propane sultone is 1.7% to 4.4% relative to the mass of the electrolyte. Preferably, the mass content of 1,3-propane sultone is 1.7% to 2.9%, and more preferably, the mass content of 1,3-propane sultone is 3.1% to 3.9%. For example, the mass content of 1,3-propane sultone may be 1.7%, 1.9%, 2.1%, 2.3%, 2.7%, 2.9%, 3.1%, 3.3%, 3.7%, 3.9%, or 4.4%, or may be a value within a range consisting of any two of these values. The inclusion of 1,3-propane sultone prevents the film formed on the graphite surface by ethyl propionate and LiFSI from being too thick, thereby further reducing the internal impedance of the secondary battery and improving the high and low temperature characteristics of the secondary battery.

[0032] electrolyte In addition to the above ethyl propionate and propyl propionate, the organic solvent in the electrolyte solution further includes some other organic solvents, which may be, but are not limited to, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), dimethyl carbonate (DMC), or propylene carbonate. In some embodiments, the other organic solvent includes an ether-based solvent, such as at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME).

[0033] In an embodiment of the present invention, the electrolyte contains a lithium salt as an electrolyte. The lithium salt in the electrolyte can be inorganic lithium salts such as LiClO4, LiAsF6, LiPF6, LiBF4, LiSbF6, LiSO3F, LiN(FSO2)2, LiCF3SO3, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,3-hexafluoropropane disulfonimide lithium, cyclic 1,2-tetrafluoroethane disulfonimide lithium, LiPF4(CF3)2, LiN(CF3SO2)(C4F9SO2), LiC(CF3SO2)3, LiPF4(CF 3SO2)2, LiPF4(C2F5)2, LiPF4(C2F5SO2)2, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2, and other fluorine-containing organic lithium salts; lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, lithium tris(oxalato)phosphate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate, and other dicarboxylic acid complex-containing lithium salts, but are not limited thereto. The lithium salts may be used alone or in combination of two or more. For example, in some embodiments, the lithium salt includes a combination of LiPF6 and LiBF4. In some embodiments, the lithium salt is LiPF6. In some embodiments, the mass content of the lithium salt in the electrolyte is 10% to 20% with respect to the mass of the electrolyte.

[0034] The electrolyte further comprises other additives. The additives in the electrolyte used in the embodiments of the present invention may be additives known in the art that can be used to enhance the electrochemical properties of the battery. In some embodiments, the additives include, but are not limited to, at least one of polynitrile compounds, sulfur-containing additives, fluoroethylene carbonate (FEC), and 1,4-butane sultone.

[0035] The method for preparing the electrolyte solution of the present invention is not limited, and may be prepared by a method for preparing an electrolyte solution in general. In some embodiments, the electrolyte solution of the present invention is prepared by mixing each component.

[0036] negative electrode In some embodiments, the graphite includes at least one of synthetic graphite or natural graphite.

[0037] The negative electrode active material particles can be obtained by selecting some petroleum coke with a relatively low volatile content as raw material, crushing it into single particles, converting it into graphite by heat treatment, and then performing surface modification treatment. Of course, the method for preparing the negative electrode active particles is not limited to this, and they can also be prepared by other methods well known in the art.

[0038] In some embodiments, the negative electrode active material layer further includes a binder, which may include various binder polymers such as polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethyleneoxy-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic acid (ester)-modified styrene butadiene rubber, epoxy resin, nylon, and the like.

[0039] In some embodiments, the negative electrode active material layer further comprises a conductive agent to improve the electrical conductivity of the electrode. Any conductive material may be used as the conductive material as long as it does not undergo chemical changes. Examples of the conductive agent may include, but are not limited to, carbon-based materials such as carbon black, acetylene black, ketjen black, and carbon fibers; metal-based materials such as metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0040] In some embodiments, the negative electrode current collector includes, but is not limited to, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and any combination thereof. In some embodiments, the negative electrode current collector is copper foil.

[0041] In some embodiments, the negative electrode structure is any negative electrode structure known in the art for use in electrochemical devices.

[0042] In some embodiments, the method for preparing the negative electrode is a method for preparing a negative electrode known in the art for use in electrochemical devices. Exemplarily, the negative electrode can be obtained by mixing the active material, the conductive agent, the binder, and the above-mentioned negative electrode additive in a solvent, optionally adding a thickener, to prepare a negative electrode active material slurry, applying the negative electrode active material slurry to a current collector, drying and cold pressing to form a negative electrode active material layer. In some embodiments, the solvent may include, but is not limited to, water and N-methylpyrrolidone.

[0043] positive electrode The positive electrode includes a positive electrode current collector and a positive electrode active material layer provided on at least one surface of the positive electrode current collector. The specific type of the positive electrode active material is not specifically limited and can be selected as necessary.

[0044] In some embodiments, the active cathode material includes a lithium transition metal complex oxide. In some embodiments, the active cathode material includes a lithium transition metal complex oxide, such as lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganate (LiMn2O4), lithium nickel manganate (LiNi 0.5 Mn 1.5 O4) and lithium iron phosphate (LiFePO4).

[0045] In some embodiments, the positive electrode active material layer further includes a binder, and optionally further includes a conductive material. The binder can enhance the bonding between the positive electrode active material particles and the positive electrode current collector. In some embodiments, the binder can include, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethyleneoxy-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic acid (ester)-modified styrene butadiene rubber, epoxy resin, and nylon.

[0046] In some embodiments, the positive electrode active material layer further includes a conductive material to provide electrical conductivity to the electrode. The conductive material may include any conductive material as long as it does not undergo chemical change. Non-limiting examples of the conductive material include carbon-based materials (e.g., carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives), and mixtures thereof.

[0047] In some embodiments, the positive current collector is a metal, including but not limited to, aluminum foil.

[0048] In some embodiments, the positive electrode structure is any positive electrode structure known in the art for use in secondary batteries.

[0049] In some embodiments, the method for preparing the positive electrode is a method for preparing a positive electrode used in a secondary battery that is well known in the art. For example, the positive electrode can be obtained by mixing an active material, a conductive material, a binder, and the above-mentioned positive electrode additive in a solvent to prepare a positive electrode active material slurry, applying the positive electrode active material slurry to a current collector, drying and cold pressing to form a positive electrode active material layer. In some embodiments, the solvent may include, but is not limited to, water, N-methylpyrrolidone, etc.

[0050] Separator In some embodiments, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator are not particularly limited and may be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic material that is stable against the electrolyte of the present invention.

[0051] For example, in some embodiments, the separator includes a substrate layer. The substrate layer is a nonwoven fabric, a film, or a composite film having a porous structure. The material of the substrate layer may be at least one selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Specifically, the material of the substrate layer may be selected from a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, and a polypropylene-polyethylene-polypropylene porous composite film.

[0052] A surface treatment layer is provided on at least one surface of the base layer. The surface treatment layer may be a polymer layer, an inorganic layer, or a layer formed by mixing a polymer and an inorganic material. Specifically, the inorganic layer includes inorganic particles and a binder. The inorganic particles may be selected from one or more combinations of alumina, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The binder may be at least one or more combinations selected from the group consisting of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene polymer, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene.

[0053] According to a second aspect of the present invention, there is provided an electronic device, the electronic device including the secondary battery described above.

[0054] The use of the secondary battery of the present invention is not particularly limited, and it can be used in any electronic device known in the prior art. For example, the electronic device includes, but is not limited to, a notebook computer, a pen-input computer, a mobile computer, an electronic book player, a mobile phone, a mobile fax machine, a mobile copy machine, a mobile printer, a headphone stereo, a video movie machine, a liquid crystal television, a handy cleaner, a portable CD, a mini disk, a transceiver, an electronic organizer, a calculator, a memory card, a mobile tape recorder, a radio, a backup power source, a motor, an automobile, a motorcycle, an assisted bicycle, a bicycle, a lighting device, a toy, a game device, a clock, an electric tool, a strobe, a camera, a large-scale household storage battery, and a lithium ion capacitor. In addition to the electronic devices listed above, the secondary battery of the present invention is also applied to an energy storage power plant, a marine transportation tool, and an air transportation tool. The air transportation device includes an air transportation device in the atmosphere and an air transportation device outside the atmosphere.

[0055] The technical solutions of the embodiments of the present invention are further illustrated below through specific examples.

[0056] Example 1-1 1. Preparation of Li-ion battery: 1. Preparation of the Negative Electrode Preparation of graphite material as negative electrode active material: Mesocarbon microbeads, which are artificial graphite, were crushed, sieved and classified to control the particle size distribution so that Dv90<25μm and Dv50=9μm, and primary particles were obtained. Bitumen, a binder, was added to the primary particles to bind them, and the particle size was controlled by sieving and classifying them to obtain secondary particles so that Dv90<45μm and Dv50=10.7μm. The primary particles and secondary particles were mixed in a number ratio of 3:7, graphitized at 2850℃ for 10h, cooled, demagnetized and sieved to obtain a graphite material with Dv50=10.2μm. The Lc of the graphite material in the negative electrode can be controlled by the particle size of the raw material and the temperature of the graphitization process.

[0057] The graphite particles, conductive carbon black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethylcellulose (CMC) prepared above were added to deionized water as a solvent in a mass ratio of 95.7:1.5:1.8:1, and mixed thoroughly to form a uniform anode slurry. The anode slurry was uniformly applied to copper foil, anode current collector, dried and cold pressed to form an anode active material layer, which was then cut and tab welded to obtain the anode.

[0058] 2. Preparation of the Positive Electrode The positive electrode active material lithium cobalt oxide, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 96.3:2.2:1.5 with the solvent N-methylpyrrolidone (NMP), and the mixture was thoroughly and uniformly stirred with a vacuum stirrer to obtain a positive electrode slurry. The positive electrode slurry was applied to an aluminum foil positive electrode current collector, dried, and cold pressed to form a positive electrode active material layer, and then cut and tab welded to obtain a positive electrode.

[0059] 3. Preparation of Electrolyte In a dry argon atmosphere glove box, propyl propionate (PP), ethyl propionate (EP), ethylene carbonate (EC) and propylene carbonate (PC) were mixed uniformly, dissolved and thoroughly stirred, and then the lithium salt LiPF6 was added and mixed uniformly to obtain an electrolyte. The mass content of the lithium salt LiPF6 was 12.5% ​​of the mass of the electrolyte, the mass content of EP was 8%, the mass content of PP was 62%, and the remaining amount was ethylene carbonate (EC) and propylene carbonate (PC), and the mass ratio of EC to PC was EC:PC=2:1.

[0060] 4. Preparation of the separator A polyethylene (PE) porous polymer film was used as the separator.

[0061] 5. Preparation of Lithium-ion Batteries A separator was placed between the positive and negative electrodes to serve as an insulator, and the resulting positive electrode, separator, and negative electrode were stacked in order and then wound up to obtain a bare cell. The bare cell was placed in an aluminum plastic film exterior foil, and an electrolyte was injected. The cell was then vacuum packaged, left to stand, and formed to obtain a lithium-ion battery.

[0062] The preparation process of Examples 1-2 to 1-13 was almost the same as that of Example 1-1, and the specific differences are shown in Table 1. The graphitization process of Examples 1-11 to 1-13 was almost the same as that of Example 1-1, but there were some differences, and the specific differences are as follows. In the graphitization process of Example 1-11, the Dv50 of the primary particles was set to 7 μm, the Dv50 of the secondary particles was set to 9 μm, and the graphitization temperature was kept at 3100° C. for 12 hours. In the graphitization process of Example 1-12, the Dv50 of the primary particles was set to 9.5 μm, the Dv50 of the secondary particles was set to 11.0 μm, and the graphitization temperature was kept at 2750° C. for 10 hours. In the graphitization process of Example 1-13, the Dv50 of the primary particles was set to 10 μm, the Dv50 of the secondary particles was set to 11.5 μm, and the graphitization temperature was kept at 2600° C. for 12 hours. The preparation processes of Comparative Examples 1-1 to 1-3 were almost the same as those of Example 1, and the specific differences are shown in Table 1.

[0063] 2.Measurement method 1. Parameter measurement: The crystallite size of the graphite material was measured by analyzing the crystallite size Lc along the vertical axis of the negative electrode graphite material using an X-ray diffractometer. From the results of X-ray diffraction measurements, the Lc value was calculated using the Scherrer formula, Lc = Kλ / β(2θ)cosθ, where K is the Scherrer constant, K = 0.9, λ is the wavelength of the incident X-rays, θ is the angle at the maximum peak value, and β is the half-width.

[0064] 2. Lithium-ion battery characteristic testing 2.1 Low-temperature discharge rate performance The lithium-ion battery was placed in a 25°C thermostatic chamber, left to stand for 5 min, discharged at a constant current of 0.5C to a voltage of 2.5V, left to stand for 30 min, charged at a constant current of 0.2C to a voltage of 3.6V, charged at a constant voltage of 0.025C, left to stand for 10 min, discharged at a constant current of 2.0C to a voltage of 2.5V (discharge capacity at 25°C), left to stand for 10 min, charged at a constant current of 0.2C to a voltage of 3.6V, and charged at a constant voltage of 0.025C. The battery was charged at a constant voltage up to 2.0 C, allowed to stand for 10 min, the temperature was adjusted to -10°C, allowed to stand for 60 min, discharged at a constant current of 1.0 C to a voltage of 2.5 V, allowed to stand for 30 min, charged at a constant current of 0.2 C to a voltage of 3.6 V, charged at a constant voltage up to a current of 0.025 C, allowed to stand for 10 min, discharged at a constant current of 2.0 C to a voltage of 2.5 V (discharge capacity at -10°C), the temperature was adjusted to 25°C, and allowed to stand for 60 min. Discharge ratio at -10°C = (discharge capacity at -10°C / discharge capacity at 25°C) x 100%. The discharge rate was 2C.

[0065] 2.2 Cycling performance at high voltage At 45°C, the lithium ion battery was charged at a constant current of 1C to a voltage of 4.4V, charged at a constant voltage of 0.05C, and then discharged at a constant current of 1C to a voltage of 3.0V, which constituted one charge / discharge cycle, and the discharge capacity of this cycle was the discharge capacity of the first cycle. The lithium ion battery was subjected to 300 cycles of charge / discharge testing using the above method, and the discharge capacity of the lithium ion battery at the 300th cycle was obtained. Cycle capacity retention rate at high voltage (%) = (discharge capacity of lithium-ion battery at 300th cycle / discharge capacity of lithium-ion battery at first cycle) x 100%.

[0066] 2.3 Measurement of high-temperature DC impedance The lithium-ion battery was placed in a thermostatic chamber at 40°C and left to stand for 2 hours. It was charged at a constant current of 0.1C to a voltage of 4.46V, charged at a constant voltage of 0.05C, and left to stand for 10 minutes. It was then discharged at a constant current of 0.1C to 3.6V, left to stand for 5 minutes, charged at a constant current of 0.1C to 4.46V, charged at a constant voltage of 0.03C, left to stand for 10 minutes, and discharged at a constant current of 0.1C for 2 hours, and the voltage V1 at this time was recorded. Next, it was discharged at a constant current of 1C for 1s (sampled every 10ms, and the current was calculated according to the nominal capacity of the lithium-ion battery), and the voltage V2 at this time was recorded. Then, the DC impedance corresponding to the 60% remaining capacity (SOC) of the lithium-ion battery was calculated.

[0067] The formula for calculating high temperature DC impedance is 60% SOC DCR=(V2-V1) / 1C.

[0068] As can be seen from Table 1, the measurement results of Examples 1-1 to 1-13 are clearly superior to the measurement results of Comparative Examples 1-1 to 1-3. Therefore, when the mass content of ethyl propionate in the electrolyte is m% and the mass content of propyl propionate is n%, by controlling the difference nm between n and m to 5 to 54, a lithium ion battery in which the Lc and n of the graphite contained in the negative electrode satisfy n / Lc of 1 to 2.14 has significantly improved low-temperature rate performance and high-temperature high-voltage performance.

[0069] The preparation process of Example 2-1 to Example 2-25 is almost the same as that of Example 1-2, and the difference is that at least one of LiFSI, LiPO2F2 and 1,3-propane sultone (PS) is selectively added to the electrolyte solution. The details of the specific differences are shown in Table 2-1 and Table 2-2.

[0070] As can be seen from Tables 2-1 and 2-2, the measurement results of Examples 2-1 to 2-25 are clearly superior to the measurement results of Example 1-2. Thus, by further adding one or more of LiFSI, PS, and LiPO2F2 to the electrolyte, the low-temperature characteristics and the performance at high temperature and high voltage of the lithium-ion battery can be improved. When the ratio of p to m, p / m, is 0.01 to 0.36, the performance of the secondary battery at high temperature and high voltage can be improved.

[0071] [Table 1] [Table 2-1] [Table 2-2]

[0072] The above embodiments are only used to describe the technical aspects of the present application, and are not limited thereto. Although the present application has been described in detail with reference to the above preferred embodiments, those skilled in the art should understand that modifications or equivalent replacements to the technical solutions of the present application do not depart from the spirit and scope of the technical solutions of the present application.

Claims

1. A secondary battery including a positive electrode, a negative electrode, and an electrolyte, The electrolyte solution includes an organic solvent, the organic solvent comprises ethyl propionate and propyl propionate; When the mass content of the ethyl propionate is m % and the mass content of the propyl propionate is n % relative to the mass of the electrolyte, the difference between n and m, nm, is 5 to 54; the negative electrode includes a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector, The negative electrode active material layer contains a negative electrode active material, The negative electrode active material contains graphite in a mass content of 90% or more, A secondary battery, characterized in that the ratio of n to the Lc value of the graphite satisfies n / Lc being 1 to 2.

14.

2. The electrolyte solution is (1) n-m is 18 to 54; and (2) m+n is 42 to 70; and (3) m is between 8 and 24; and (4) n is 29 to 62; and (5) n / Lc is 1.10 to 2.00; The secondary battery according to claim 1 , wherein at least one of the above conditions is satisfied.

3. The electrolyte solution is (6) n-m is 21 to 47; and (7) m+n is 53 to 69; and (8) m is 8 to 19; and (9) n is 33 to 58; and The secondary battery according to claim 1 , wherein at least one of the above conditions is satisfied.

4. The electrolyte solution is (I) m+n is 52 to 67.5; (II) m is 11 to 21; (III) n is 30 to 53.5; The secondary battery according to claim 1 , wherein at least one of the above conditions is satisfied.

5. The electrolyte further comprises lithium bis(fluorosulfonyl)imide; 2. The secondary battery according to claim 1, wherein p is a mass content of the lithium bis(fluorosulfonyl)imide relative to the mass of the electrolyte, and p is 0.07 to 4.

3.

6. 6. The secondary battery according to claim 5, wherein a ratio of p to m, p / m, is 0.01 to 0.

36.

7. The electrolyte solution is (I) p is 0.7 to 2.4; (II) p / m is 0.07 to 0.17; The secondary battery according to claim 5 , wherein at least one of the above conditions is satisfied.

8. The electrolyte solution is (III) p is 1.3 to 3.5; (iv) p / m is 0.09 to 0.32; The secondary battery according to claim 5 , wherein at least one of the above conditions is satisfied.

9. 2. The secondary battery according to claim 1, wherein the Lc value of the graphite is 25 to 38.

10. The secondary battery according to claim 1 , wherein the graphite includes at least one of artificial graphite and natural graphite.

11. The electrolyte solution is (a) the electrolytic solution further contains lithium difluorophosphate, and the mass content of the lithium difluorophosphate is 0.02% to 2.4% relative to the mass of the electrolytic solution; (b) the electrolytic solution further contains 1,3-propane sultone, and the mass content of the 1,3-propane sultone is 1.7% to 4.4% relative to the mass of the electrolytic solution; The secondary battery according to claim 1 , wherein at least one of the above conditions is satisfied.

12. The electrolyte solution is (c) the electrolytic solution further contains lithium difluorophosphate, and the mass content of the lithium difluorophosphate is 0.2% to 1.6% with respect to the mass of the electrolytic solution; (d) the electrolytic solution further contains 1,3-propane sultone, and the mass content of the 1,3-propane sultone is 1.7% to 2.9% relative to the mass of the electrolytic solution; The secondary battery according to claim 1 , wherein at least one of the above conditions is satisfied.

13. The secondary battery according to claim 11, wherein the electrolyte contains 1,3-propane sultone, and the mass content of the 1,3-propane sultone is 3.1% to 3.9%.

14. An electronic device comprising the secondary battery according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Lithium secondary cell and nonaqueous electrolytic solution for use therein

    CN101292389A

  • Electrochemical device and electronic device

    CN115735283A

  • Negative active material, negative pole piece, battery and electric device

    CN116826019A

  • Negative electrode active material, and electrochemical device and electronic device using the same

    JP2022539930A

  • Negative electrodes for lithium-ion secondary batteries

    JP2023528519A